Assessment of growth and physiological effects of dietary Arthrospira platensis in broiler chickens - Zain Ul Abideen; Muhammad Zeshan Haider; Muhammad Kashif Zaman; Muhammad Farooq; Amin F. Majdalawieh; Imad A. Abu-Yousef; Tahira Ruby; Aleem Ahmed Khan (Livestock Science, 2026)

Correction: Neratinib-loaded solid lipid nanoparticles in dissolvable microneedles for enhanced transdermal breast cancer therapy - Saraisam Kishor Kumar Singha; Venkatesh Dinnekere Puttegowda; Yousef Al-ebini; Mohamed Rahamathulla; Joysa Ruby Joseph; Ajay Pankajbhai Lunagariya; Mohammed Jafar; Syeda Ayesha Farhana; Manjunatha Panduranga Mudughal; Gowdru Vishwanath Nahusha; Mohammed Muqtader Ahmed (Drug Delivery and Translational Research, 2026)

Neratinib-loaded solid lipid nanoparticles in dissolvable microneedles for enhanced transdermal breast cancer therapy - Saraisam Kishor Kumar Singha; Venkatesh Dinnekere Puttegowda; Yousef Al-ebini; Mohamed Rahamathulla; Joysa Ruby Joseph; Ajay Pankajbhai Lunagariya; Mohammed Jafar; Syeda Ayesha Farhana; Manjunatha Panduranga Mudughal; Gowdru Vishwanath Nahusha; Mohammed Muqtader Ahmed (Drug Delivery and Translational Research, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

A holistic guide to effective prevention and treatment for kidney stones: a systematic review exploring anti-urolithiasis approaches - Anood T. Allam; Ahmed M. El-Dessouki; Riham A. El-Shiekh; Dina Abou-Hussein; Mahmoud Abdelmouti Mahmoud; Wagih H. Marcus; Hassan A. Ruby (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)
Urolithiasis, a disease of kidney stones, is a prevalent and recurrent condition characterized by the formation of hard mineral deposits in the urinary tract, leading to significant morbidity and a substantial healthcare burden worldwide. With recurrence rates ranging from 30 to 50% and a lifetime prevalence of 9–12% in industrialized populations, effective prevention and management strategies are crucial. Traditional approaches to urolithiasis, including pharmacological agents and surgical interventions, emphasize medical interventions and lifestyle changes; however, the persistent recurrence and impact on quality of life underscore the necessity for more comprehensive solutions. Recent advancements have focused on the potential of nutraceuticals, including herbal extracts, vitamins, and minerals, as adjuncts in the prevention and treatment of kidney stones. These agents may exert beneficial effects by inhibiting stone crystal formation, modulating urinary pH, reducing urinary calcium and oxalate excretion, enhancing diuresis, and supporting overall renal function. Moreover, these plant-based therapies may help alleviate symptoms such as pain and inflammation related to stone episodes. This systematic review synthesizes findings from 14 randomized controlled trials to assess the therapeutic impact and safety profile of various herbal interventions in patients with diagnosed kidney or ureteral stones. Thus, evidence from these recent clinical trials has increasingly supported the efficacy of single-herb and polyherbal formulations, such as Nigella sativa , Alhagi maurorum , Subap Plus, and Palasha Kshara, in modulating urinary risk factors and promoting stone expulsion. For instance, these trials demonstrated promising outcomes for several herbs: Portulaca oleracea significantly increased urinary citrate and reduced calcium, Traditional Persian Medicine-based Mofatet powder markedly reduced stone size and improved urinary parameters, Alhagi maurorum distillates and extracts showed comparable efficacy to hydrochlorothiazide in stone expulsion, and Nigella sativa performed as well as or better than tamsulosin in both pain relief and stone passage. Additional polyherbal remedies, such as Subap Plus, Palasha Kshara, and BNO 1040 extract, also yielded favourable results in improving stone clearance, easing symptoms, and potentially preventing recurrence. Notably, most studies reported good short-term tolerability and minimal adverse effects. Despite these promising findings, limitations in sample size, standardization of formulations, lack of comprehensive adverse events reporting, and need for long-term follow-up highlight the necessity for further rigorous trials.

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Alkyl Chain-Tuned Fluorescent Sensors: Phenanthroimidazole Derivatives for Selective Detection of Nitroaromatic Compounds Containing Phenolic Group - Mohd Tameem; Abid Ali; Ruby Ahmed; Farman Ali; Nagmajahan; Musheer Ahmad (Journal of Fluorescence, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Influence of seasonal variation on steroidal content and in vivo post-coital antifertility activity of bark extracts of Caesalpinia pulcherrima Linn - Benson Mathai Kochikuzhyil; Mansour Almuqbil; Syed Mohammed Basheeruddin Asdaq; Abdul Rahim Huma; Ruby Benson; Kuntal Das; Majeshwar Shrinath Baliga; Subash Philip; Ahmed Alshehri; Adel Alghamdi; Moneer E. Almadani; Farhana Yasmin; et al. (South African Journal of Botany, 2024)

Multidisiplinary design optimization of a power generation system based on waste energy recovery from an internal combustion engine using organic Rankine cycle and thermoelectric generator - Abdeljelil Chammam; Abhishek Kumar Tripathi; Abrahan-Pablo Aslla-Quispe; Yersi-Luis Huamán-Romaní; Sherzod Shukhratovich Abdullaev; Naseer Ali Hussien; Ahmed Alkhayyat; Ali hashim Alsalamy; Ruby Pant (Chemosphere, 2023)

Glomus fasciculatum an arbuscular mycorrhizal fungus alleviate the adverse effects of lead, arsenic, nickel, and improves growth parameters of Monarda citriodora Cerv.ex Lag (lemon beebalm) - Savita Luxmi; Ruby Singh; Sajad Ahmed; Sumit G. Gandhi; Rajendra Bhanwaria (Rhizosphere, 2023)

Analysis of positive correlation in magnitude and time measurement for earthquake using electric signals - Oumaima Saidani; Ramkumar Raja Manoharan; Ahmed Samir Naje; Ruby Mishra; Arjun Subburaj; Maheswari S; Mohamed Yacin Sikkandar; Sankar Ganesh Sundaram; Regin Rajan; Sudhakar Sengan (Earth Science Informatics, 2022)

Antimicrobial, antioxidant, antiviral activity, and gas chromatographic analysis of Varanus griseus oil extracts - Shakeel Ahmad; Tahira Ruby; Mirza Imran Shahzad; Gildardo Rivera; Diana Victoria Navarrete Carriola; Aleem Ahmed Khan (Archives of Microbiology, 2022)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)